Impact of each release parameter on pitch location in baseball pitching - Nasu, D.; Kashino, M. (Journal of Sports Sciences, 2021)
This study investigated the amount of impact of each release parameter - pitch speed, release position, release projection angle and spin rate and axis - on pitch location during four-seam fastball pitching. Data from 26 pitchers, including professionals, semi-professionals and collegiate pitchers, were obtained by using simplified radar ball-tracking system called TrackMan Baseball. The results of a multiple linear regression analysis indicate that the release projection angle had the largest effect on the pitch locations and the spin rate had the smallest effect among significant predictor variables in both vertical and horizontal planes. The amounts of change in pitch location affected by 1-SD changes in release projection angles in vertical and horizontal planes (0.73° and 0.69°, respectively) were both about half of home-plate width (19.8 cm and 18.2 cm); those affected by 1-SD changes in the spin rate (67.7 rpm) were both about 1/10 of the size of a baseball (0.83 cm and 0.75 cm). The results of this study are concrete indicators for coaches and players when they use a ball-tracking system and interpret the measured data.